23-gauge vitrectomy with intraocular foreign body removal via the limbus: An alternative approach for select cases - Ramandeep Singh; Swapnil Bhalekar; Mangat R Dogra; Amod Gupta (Indian Journal of Ophthalmology, 2014)
Purpose: To study the outcome of removal of retained intraocular foreign bodies (RIOFBs) via limbus using 23-gauge transconjunctival sutureless vitrectomy (TSV). Materials and Methods: In this prospective, non-comparative interventional case series, fourteen eyes of 14 patients fulfilling the inclusion criteria were enrolled. They underwent 23-gauge TSV for management of posterior segment RIOFB and reviewed at 1 day, 7 days, 6 weeks, 3, 6 and 12 months. Eyes with penetrating eye injury involving cornea or limbus (corneal injury not so severe to hinder vitrectomy), cataract associated with anterior and/or posterior capsular tear requiring cataract surgery and posterior segment RIOFB with minimal posterior segment involvement were included. Main outcome measures include success in removal of RIOFB without enlarging sclerotomy, ability to preserve capsular support, improvement in visual acuity and complications, if any. Results: All eyes underwent the successful RIOFB removal through limbal port without enlarging scleral ports. None of the eyes required suturing of the sclera, cornea or conjunctiva. Anterior capsular rim could be preserved in all eyes except one. Postoperatively follow up ranged from one year in 8, 6 months in 4 and 3 months in 2 eyes. The mean logMAR visual acuity at 3, 6, and 12 months showed significant improvement. There were no intraoperative complications. Postoperative complications include microscopic hyphema and loose blood in vitreous cavity in one eye. Conclusion: The advantages of 23-gauge TSV for removal of RIOFB may be passed on to select cases. RIOFB removal through limbal route obviated the need for scleral port enlargement and preserved capsular support for early visual rehabilitation.